2007
DOI: 10.1245/s10434-007-9562-x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Prognostic Significance of RhoA and RhoC Gene Expression in Esophageal Squamous Cell Carcinoma

Abstract: To our knowledge, this study is the first in which the expression of RhoA and RhoC at the mRNA level in ESCC was examined and compared with its normal counterpart. Our results suggest that rhoA and rhoC are involved in ESCC progression and useful as prognostic markers. Further study will be needed to examine the therapeutic potential of the Rho GTPase inhibitor as a promising anticancer therapy, especially in ESCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
34
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 29 publications
4
34
0
2
Order By: Relevance
“…Enhanced RhoA activity in the cancer cells is mostly due to RhoA overexpression because mutation of RhoA has not been found in human cancers (33,34). Accumulating evidences have shown that upregulation of RhoA mRNA and RhoA protein levels has been well documented in various human cancers (29,30,35). The present study suggests one potent mechanism of epithelial RhoA overexpression via wound-induced NAG-1.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Enhanced RhoA activity in the cancer cells is mostly due to RhoA overexpression because mutation of RhoA has not been found in human cancers (33,34). Accumulating evidences have shown that upregulation of RhoA mRNA and RhoA protein levels has been well documented in various human cancers (29,30,35). The present study suggests one potent mechanism of epithelial RhoA overexpression via wound-induced NAG-1.…”
Section: Discussionsupporting
confidence: 58%
“…In contrast, the current study observed elevation of total level of RhoA protein. Upregulation of RhoA expression has been also observed in various types of human cancer cells (29)(30)(31), and one suggested deciphering of the oncogenic induction of RhoA expression is the signaling orchestration by Myc-Skp2-Miz1-p300 transcriptional complex (32). Enhanced RhoA activity in the cancer cells is mostly due to RhoA overexpression because mutation of RhoA has not been found in human cancers (33,34).…”
Section: Discussionmentioning
confidence: 99%
“…Rho has been linked to increased cell proliferation in many cancers, in which it is increased in both amount and activation state (Faried et al, 2007;Sterpetti et al, 2006;Wang, H. B. et al, 2009;Zhang et al, 2009). Mammary carcinoma cells proliferate in response to stiff matrices, and this was shown to be mediated in part by Rho (Paszek et al, 2005;Provenzano et al, 2009;Wozniak et al, 2003).…”
Section: Journal Of Cell Sciencementioning
confidence: 99%
“…RhoA and RhoC have been extensively documented for migration and invasion (Faried et al, 2007;Liu et al, 2012;Struckhoff et al, 2011). RhoA expression is increased in human breast cancers due to miRNAmiR-31 suppression, and metastasis in mouse models has also been reported (Valastyan et al, 2009).…”
Section: Discussionmentioning
confidence: 99%